Strategizing hospitality internship for effective implementation: perspectives of internship coordinators - Soffi, Muhammad Nazreen Ezyan; Mohamad, Siti Fatimah (Human Resource Management Academic Research Society, 2021)
An internship is an experiential learning process where undergraduates have to undergo practical training in a chosen organization. The primary purpose of an internship is to allow the undergraduates to apply knowledge and skills they have learned in classrooms, thus achieving thorough learning of the subject matter. However, there are challenges in an internship, not only to interns but also to coordinators who plan and manage the internship implementation. The internship challenges have been well-studied, but the strategies to overcome the challenges should be planned according to the internship context, such as the program study and region. Hence, this paper aimed to identify strategies applied by universities in escalating undergraduates’ competencies through an effective hospitality internship program. This study employed a qualitative approach by conducting semistructured interviews with the internship coordinators who had experiences in handling hospitality internship in Malaysian public universities. The instrument was developed based on the literature review and discussion with the experts. There were seven internship coordinators interviewed in this study, and the findings were analyzed using thematic analysis with the help of ATLAS.ti 8 software. This study proposed five strategies used in the public universities to escalate the effectiveness of the hospitality internship implementation: i) communication, ii) revision, iii) networking, iv) blocklist and v) guidance. The findings are expected to add value not only to the current literature within the hospitality field but also to all the stakeholders of the internship program, particularly in Malaysian public universities, to structuring a successful and effective internship program.